2013
DOI: 10.2753/csa2162-0555460104
|View full text |Cite
|
Sign up to set email alerts
|

"Bare Branches" and the Marriage Market in Rural China

Abstract: Using data from a village survey in rural China, this study explores the relationships between current prevalence of involuntary bachelorhood and its causes and social consequences at the village level. We find that bachelors, inter-county marriage and marriage fraud exist in all regions, and are expected to become more frequent with the increasing surplus of males born after 1980 entering the marriage market. The marriage squeeze and social problems related to the bachelors are more serious in less-developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Three townships in each county were selected according to their levels of economic development. These areas contain the highest levels of "bare branches" in China, as previous studies showed that the "bare branches" were concentrated mainly in underdeveloped regions of China, especially in rural areas of Western China (Das Gupta et al, 2010;Jin et al, 2013). The "bare branches" in these areas could help us to understand a deeper level of the "bare branches" in China.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Three townships in each county were selected according to their levels of economic development. These areas contain the highest levels of "bare branches" in China, as previous studies showed that the "bare branches" were concentrated mainly in underdeveloped regions of China, especially in rural areas of Western China (Das Gupta et al, 2010;Jin et al, 2013). The "bare branches" in these areas could help us to understand a deeper level of the "bare branches" in China.…”
Section: Methodsmentioning
confidence: 92%
“…It has been estimated that the number of "bare branches" has reached above 30 million and this number is likely to increase after 2030 due to the one child per couple policy (OCP; Ebenstein & Sharygin, 2009;Jiang, Guo, & Li, 2010). "Bare branches" mainly live in less developed rural areas and poorer households in China, where vulnerable groups have a higher dependence on family support due to low levels of state support or social protection (Das Gupta, Ebenstein, & Sharygin, 2010;Jin, Liu, Feldman, & Li, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[34,47,48]). The work by Jin et al [49] provided one clue, presumably unique to China, as to the transition in sex preference for children: in current China, there is a very high economic cost for men to marry in a context of a surplus of men and a shortage of marriageable women, which might make parents very reluctant to have more than one son, especially in rural areas. The strong practical burden of parenting sons also helps to explain the significant negative effect of having two sons on post-second birth life satisfaction, a result in contrast to that of Margolis and Myrskylä [47], who found little effect of sex preference on parental subjective well-being in European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Co-residing with parents and emotional ties with parents are not the determinants of children’s remaining unmarried, but terminating a child’s bachelorhood by marriage is regarded as essential for continuity of the male line and as the main source of old-age support for parents. Indeed, childlessness is an unforgivable sin in Chinese Confucian ideology concerning filial piety (Jin, et al, 2013; Liu et al, 2014; Zhang & Zhong, 2005). …”
Section: Discussionmentioning
confidence: 99%